2014
DOI: 10.1017/s1368980014000263
|View full text |Cite
|
Sign up to set email alerts
|

Vegetarian diets and cardiovascular risk factors in black members of the Adventist Health Study-2

Abstract: Objective To compare cardiovascular risk factors between vegetarians and non-vegetarians in black individuals living in the USA. Design A cross-sectional analysis of a sub-set of 592 black women and men enrolled in the Adventist Health Study-2 (AHS-2) cohort of Seventh-day Adventists. Setting Members of the AHS-2 cohort, who lived in all states of the USA and provinces of Canada. Subjects Black/African-American members of two sub-studies of AHS-2 where blood and physiological measurements were obtained. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
63
2
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 57 publications
8
63
2
7
Order By: Relevance
“…[37][38][39] Some trials have reported lowering of high-density lipoprotein cholesterol concentrations and the ratio of total cholesterol to high-density lipoprotein. 40 Vegetarian dietary patterns are characterized as predominantly including fruits, vegetables, whole grains, and nuts, similar to the DASH diet. Whether vegetarian diets, with or without dairy products, achieve benefits similar to those of the DASH diet is unknown.…”
Section: The Vegetarian Dietary Pattern: Nutrient Dense Variably Defmentioning
confidence: 99%
“…[37][38][39] Some trials have reported lowering of high-density lipoprotein cholesterol concentrations and the ratio of total cholesterol to high-density lipoprotein. 40 Vegetarian dietary patterns are characterized as predominantly including fruits, vegetables, whole grains, and nuts, similar to the DASH diet. Whether vegetarian diets, with or without dairy products, achieve benefits similar to those of the DASH diet is unknown.…”
Section: The Vegetarian Dietary Pattern: Nutrient Dense Variably Defmentioning
confidence: 99%
“…Based on growing evidence, [10][11][12][13][14][15] it has been recommended that physicians encourage patients to consume plant-based diets. 16 The aim of this investigation was to evaluate the effectiveness of a defined, plant-based diet as an adjunct to or replacement of prescription drugs in the treatment of hypercholesterolemia and HTN in an outpatient clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…5 The proportion of deaths due to CVDs in Asians may be about 15% and in India CVD accounts for 53.5% of mortality. 1,4 A constellation of modifiable (smoking, hypertension, diabetes mellitus, anthropometric parameters, metabolic parameters like lipid profile) and non-modifiable factors (age, gender) interact together to substantially increase the risk of CVD.…”
mentioning
confidence: 99%
“…1,6 Various studies show that there is association between high serum cholesterol levels, triglyceride levels and the prevalence of myocardial infarction and cerebral vascular accidents. 7 Also, evidence is present to show that vegetarian diet plays significant role in vascular protection and consumption of vegetarian diet reduces the risk of CVD.…”
mentioning
confidence: 99%
See 1 more Smart Citation